Exploring the self-reported perspectives and behaviors of predominantly English-speaking teachers regarding the incorporation of English language learners’ native languages into instruction - Karathanos, Katya A. (Kansas State University, 2005)
Research shows the practice of incorporating English language learner (ELL) students’ native languages (L1) into instruction to be a major factor enhancing their success in school. In this study, 327 predominantly English-speaking (PES) teachers in the state of Kansas were surveyed on their perspectives and self-reported behaviors related to this practice. Participants were divided among three targeted teacher groups: pre-service teachers with no ESL-specific university preparation (PS), experienced teachers with no ESL-specific university preparation (No-ESL), and experienced teachers with significant (at least three courses) ESL-specific university preparation (C-ESL). Findings from descriptive analyses indicated that while teachers generally supported L1 use in instruction, they tended to show stronger support for its underlying theory than for its practical implementation. Results from a series of ANOVA’s suggested a clear link between ESL-specific university preparation and an increased support for the theory and practice of L1 use in instruction. Findings further suggested links among some combination of teaching experience and an increase in support for this practice. A series of inter-correlations produced various modest to moderate significant relationships among experienced teachers’ perspectives and demographic variables (gender, experience with ELL students). While both No-ESL and C-ESL teachers reported behaviors incorporating L1 use into instruction to some degree, results from independent samples t-tests showed that CESL teachers reported these behaviors significantly more often than No-ESL teachers. For both experienced teacher groups, inter-correlations showed modest to moderate significant relationships among a number of perspective items and behavior items. Results further indicated that although both groups shared some common relationships among variables, for the most part, the relationships shown to be significant varied considerably by group. Open-ended questions revealed a variety of approaches used by teachers as well as a number of obstacles perceived by teachers in incorporating L1 use in instruction. Findings from this study are discussed in relation to strategies and directions for teacher educators with the responsibility of preparing PES teachers to effectively serve increasing ELL student populations.
Keywords: ELL; Teacher perspectives, beliefs, attitudes and knowledge; Native language; English speaking; ESL; Education, Bilingual and Multicultural (0282)